2022
DOI: 10.1111/famp.12757
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent problematic Internet use and parental involvement: The chain mediating effects of parenting stress and parental expectations across early, middle, and late adolescence

Abstract: Problematic Internet use (PIU), a common phenomenon, has negative effects on adolescents, especially during the COVID-19 pandemic. Adolescents with PIU pose great challenges to parenting. However, little is known about the mediating mechanisms underlying this relationship.The study examines the chain mediating roles of parenting stress and parental expectations between PIU and parental involvement across early, middle, and late adolescence.Families (N = 1206) that included fathers, mothers, and adolescents (48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 88 publications
0
24
0
1
Order By: Relevance
“…Or does higher education involvement reduce parenting anxiety or stress? To solve these questions, it is suggested that future research further investigate the influence of parental involvement on parents' emotions (e.g., Liu et al, 2022). Finally, the cross-sectional data used in this study have some deficiencies in the discussion of the causal relationship between variables.…”
Section: Limitationsmentioning
confidence: 97%
“…Or does higher education involvement reduce parenting anxiety or stress? To solve these questions, it is suggested that future research further investigate the influence of parental involvement on parents' emotions (e.g., Liu et al, 2022). Finally, the cross-sectional data used in this study have some deficiencies in the discussion of the causal relationship between variables.…”
Section: Limitationsmentioning
confidence: 97%
“…Adopting a two-wave longitudinal study, Koning et al (2018) found that excessive Internet use would lead to a lower frequency and poorer quality of parent-child conflict communication. In China, there were also several empirical studies demonstrated that adolescents with IA often posed great challenges to their parents, introduced a series of parenting stress (Liu et al, 2022), and resulted in incessant family conflict through the parent-adolescent subsystem (Wang et al, 2011). Thus, from the perspective of the "below" pressure hypothesis and related empirical research, adolescent IA might impair or deteriorate family function, leaving the family system more vulnerable to getting into dysfunctional state.…”
Section: Directional Effect Between Family Dysfunction and Adolescent Iamentioning
confidence: 99%
“…Moreover, harsh parenting was not signi cantly related to self-kindness and not directly related to adolescent well-being in late adolescence. The decreasing susceptibility of adolescent well-being toward harsh parenting can be attributed to the more salient developmental autonomy in late adolescence (Liu et al, 2022;Shek et al, 2021). As adolescents grow older, they may become more independent (Liu et al, 2022) and less likely to be affected by others.…”
Section: Developmental Differencesmentioning
confidence: 99%
“…The participants' mean age was 13.53 (SD = 2.08). Adolescents belong to three developmental stages (Liu et al, 2022;Zou et al, 2020), including early (10-12 years old, N = 5055), middle (13-15 years old, N = 6714), and late adolescence (16-18 years old, N = 3007). In the sample, 25.6% of the participants were the only children in their families.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation